FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT MAHASISWA IAIN SURAKARTA DALAM MEMILIH PERBANKAN SYARIAH - Siti Fatimah; Maya Novitasari; Emy Muslimah (Universitas Islam Negeri Raden Mas Said Surakarta, 2019)
This study aims to determine whether there is a relationship between variables related to the results of student interest in choosing a islamic banking. The samples involved in the research were IAIN Surakarta students. Data were analyzed by using SPSS with multiple regression, so it can be known there is or no relation between independent variable with dependent variable. Independent variables in this study Includes gender, age, understanding law of usury, religious, social environment, and family. Meanwhile, for the dependent variable is student interest in choosing a islamic banking. Based on this study, the independent variables that significantly influence the dependent Â variables there is only one, namely the understanding of usury law.Â Keywords:Â independent variable; dependent variable; islamic bank; IAIN Surakarta